ТИЖОРАТ БАНКЛАРИДА КРЕДИТ РИСКЛАРИНИ КАМАЙТИРИШ АМАЛИЁТИНИ ТАКОМИЛЛАШТИРИШ - Абдумуталибов Умиджон Абдувахоб уғли, Хикматов Илёсжон Умаржонович (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article discusses the issues of increasing the effectiveness of mechanisms related to credit risk management in the loan portfolio of commercial banks. We know that banking is a risk-based activity. The tasks of risk management in banking have always been very important. In this regard, the most pressing issue of the banking system is to improve the quality of corporate governance and the implementation of risk management procedures in the current activities of banks.